Doppler study of middle cerebral artery and umbilical artery in biometrically suspected intra uterine growth restricted pregnancies - Kuber, Rajesh; Randhawa, Shubreet; Khaladkar, Sanjay; Patil, Abhijit M. (International Journal of Research in Medical Sciences, 2016)
Background: Intra uterine growth restricted (IUGR) is when the expected foetal weight is less than 10th percentile for gestational age. The hemodynamics of the feotus takes into account both the umbilical-placental and cerebral vascular beds. Underlying etiology that results in the failure of a foetus to attain its expected growth may vary. However the final infliction is via uteroplacental insufficiency. It is highlighted that inadequate uteroplacental perfusion is the main and primary pathology in growth restriction resulting in an increased umbilical artery impedance. Following this step are the changes in the middle cerebral artery (MCA) which categorically set in as a secondary phenomenon. Methods: Duplex Doppler Sonography is a reliable, non- invasive and rapid diagnostic technique in IUGR patients. Grey scale findings together with colour Doppler characteristics help in the qualitative as well as quantitative evaluation of the Uteroplacental and Fetoplacental circulation. Hence ultrasonography (USG) has become the most widely used, standard and simple way of detecting and confirming IUGR. Ultrasound biometry is the gold standard for assessment of foetal size. Various criteria are used to label a feotus growth restricted; foetal weight less than 10th percentile for gestational age is mostly widely accepted criterion. Others like elevated HC/AC ratio, elevated FL/AC ratio, and presence of oligohydramnios without ruptured membranes, presence of advanced placental grade can also be used for improving the accuracy of diagnosis. After establishing the diagnosis of IUGR, Doppler imaging becomes a valuable investigating method for monitoring the pregnancy because it provides information about the hemodynamic status of the feotus. Uteroplacental system evaluation takes into account the flow pattern of uterine artery, reflecting any underlying Uteroplacental vascular ischemia. Umbilical artery Doppler waveforms reflect the status of the fetoplacental circulation and any underlying placental insufficiency. Results: Fourteen cases showed absent umbilical artery end diastolic flow and four patients showed reversal of end diastolic flow.: Twenty two patients showed elevated PI. Adverse perinatal outcome was observed in all patients with absent and reversal of end diastolic flow. Out of the twenty two with elevated PI fifteen showed adverse outcome. Thirty six cases showed low MCA PI and six showed a pseudonormalization. A cerebro -placental ratio of < 1.08 was observed in 16 patients, it was calculated in only those pregnancies that showed forward diastolic flow in umbilical artery (n= 22). Fifteen of them showed adverse perinatal outcome. Conclusions: Doppler imaging is of value for monitoring pregnancies complicated with IUGR because it can provide indirect evidence of foetal compromise and is known to improve outcome of high risk pregnancies. Doppler evaluation is complementary to all other surveillance modalities. Because the changes in umbilical, uterine & MCA strongly correlate with pregnancy outcome in growth restricted foetuses the use of foetal biometry & Doppler examination is recommended in all cases of suspected IUGR cases.